'Putting themselves out there' into the unknown: Dance movement psychotherapy as perceived by five educators and three pupils. Issue 4 (2nd October 2018) - Parsons, Ailsa Shaw; Dubrow-Marshall, Linda
ABSTRACT: The introduction of dance movement psychotherapy (DMP) to a mainstream secondary school in the United Kingdom was explored from the perspectives of some educators (n = 5) and pupil-clients (n = 3) to discover perceptions of, and influences on the process of establishing a DMP practice to support pupils within this setting. Semi-structured interviews were analysed using constructivist grounded theory by an ethnographically situated therapist-researcher. Two polarities of themes emerged: constraints, normative inhibitions and expectations, versus empowerment, novel perceptions and awareness . These polarities were evident at two levels of process: school structures and community mind-set and individual engagement with DMP . The results highlight inherent dynamics in positioning of therapeutic provision within a school environment, amplified in unconventional, creative and embodied forms of intervention. An awareness of the tension between these opposites may be useful for dance movement psychotherapists in setting themselves within mainstream education.